Consumer perception of rebranding in the automotive industry in the Czech Republic : The case of Škoda Auto - Chudobova, Claire (2025)
This thesis explores the multifaceted dynamics of rebranding within the automotive industry, with a specific focus on Škoda Auto. The study employs qualitative research methods to delve into Czech car customer perceptions of Škoda Auto's recent rebranding initiative, aiming to uncover insights into its impact on customer perception, purchase intention and loyalty of a brand heritage. Against the backdrop of a rapidly evolving automotive landscape and increased global competition, Škoda Auto undertook a significant rebranding effort, altering its corporate identity. The research is structured around the pivotal themes of customer sentiment, loyalty, and the preservation of brand heritage in the face of modernization. The qualitative study, conducted through in-depth interviews, captures a diverse range of Czech car drivers’ opinions spanning from different age groups, professional backgrounds, and car brand affiliations. Initial findings reveal a somewhat neutral reaction to the change, as Czech car drivers grapple with the balance between modernization and the preservation of Škoda Auto's rich brand heritage. Notably, the study highlights the role of brand heritage and brand familiarity as crucial for Czech car customers, especially among older demographics, where rebranding plays no major role on customers’ behavior. In essence, this thesis contributes to the evolving discourse on rebranding in the automotive sector, offering a nuanced understanding of customer attitudes toward brand evolution of a legacy brand. By diving into what drives Czech car customers when it comes to corporate identity of a brand they are somewhat attached to, this study provides actionable insights for carmakers, helping them navigate the intricacies of rebranding in a highly competitive and ever-changing market.